FIGURATIVE LANGUAGES USED IN EMILY DICKINSON DEATH POEMS FIGURATIVE LANGUAGES USED IN EMILY DICKINSON DEATH POEMS FIGURATIVE LANGUAGES USED IN EMILY DICKINSON DEATH POEMS - YUNIARIANDINI, AMANTA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study aims to find out the figurative language used and its meaning inEmily Dickinson death poem. There are two research problems in this study,namely: (1) the types of figure of speech used in Emily’s death poems, and (2) themeaning of figure of speech that Emily used.This study uses qualitative approach in term of document or contentanalysis because it focuses on identifying and analyzing the figure of speech inEmily Dickinson death poem. This study applies the theory of Figure of speechproposed by Pierce (1969).This study reveals twelve types of figure of speech stated in Pierce’stheory, Emily commonly uses only six figures of speech like: personification,metaphor, simile, synecdoche, symbol and paradox. Emily uses that figure ofspeech to describe the abstract feeling of death.In the first poem entitled “I Heard a Fly Buzz When I Died”, the writerfinds three personifications, one simile, one synecdoche, and five symbols. In“I’ve Seen a Dying Eye” there are one personification, one simile, onesynecdoche and three symbols. The third poem is “Because I could not Stop forDeath”, this poem has four personifications, two metaphors, one synecdoche andfour symbols. The next poem is “My Life Closed Twice before Its Close” foundone personification, one simile, four symbols and one paradox. The fifth poem “INever Lost as Much but Twice”, the writer found one personification and fivesymbols. In “I Felt a Funeral in My Brain” there are one personification, twometaphors, two similes, and two symbols. The last poem “I Died for Beauty” hasfour personifications and three symbols.The writer suggests the next researchers can cover the limitations of thisstudy by taking further research. The next researcher can also apply semanticstudy about figure of speech in other objects, in example advertisement, sloganand poetry. Key words: Figurative language, Emily Dickinson, Poems